A PHILOSOPHICAL LOOK INTO THE COSMOS - Marco Russo (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2011)
The aim of this paper is to show why the cosmos has been an important theme in the philosophical tradition. With the aid of some historical and conceptual references, we illustrate what it means that the human experience has a cosmological character: the close relationship between the world and the cosmos, the origins of Logos and astronomy, between the universe and the knowledge of human beings, the moral meaning of contemplatio caeli as an "elevation" above human concerns. For a number of reasons, this tradition has fallen into obscurity. The conquest of space has no spiritual relevance anymore; there is a gap between the cosmos and the world, as if they were different things. The remembrance of that relevance aims to create an incentive of a new cultural background of extraterrestrial experience.